Influence of a rocky platform in the profile morphology: Victoria Beach, Cadiz (Spain) - AM Bernabeu-Tello; JJ Muñoz-Pérez; R Medina-Santamaría (Ciencias Marinas, 2002)
The equilibrium profile concept is a useful tool for the knowledge and management of the coastline. This concept is based on several assumptions that rarely are satisfied in nature. One of these considers that the geologic setting has no influence in the profile morphology. The Victoria beach is a good example that questions this hypothesis. Muñoz-Pérez (1996) and Muñoz-Pérez et al. (1999) proposed an analytical expression of equilibrium beach profile for reefprotected beaches. In this work, data measured at Victoria beach are used to confirm the goodness of this model. The results obtained show that the occurrence of a horizontal rocky platform in subtidal zone modifies the beach slope and the seasonal evolution of the profile.